Stat3 Signaling Pathway: A Future Therapeutic Target for Bone-Related Diseases - Li, Jiadong; Yin, Zhifeng; Huang, Biaotong; Xu, Ke; Su, Jiacan (Frontiers in Pharmacology, 2022)
Signal transducer and activator of transcription 3 (Stat3) is activated by phosphorylation and translocated to the nucleus to participate in the transcriptional regulation of DNA. Increasing evidences point that aberrant activation or deletion of the Stat3 plays a critical role in a broad range of pathological processes including immune escape, tumorigenesis, and inflammation. In the bone microenvironment, Stat3 acts as a common downstream response protein for multiple cytokines and is engaged in the modulation of cellular proliferation and intercellular interactions. Stat3 has direct impacts on disease progression by regulating mesenchymal stem cells differentiation, osteoclast activation, macrophage polarization, angiogenesis, and cartilage degradation. Here, we describe the theoretical basis and key roles of Stat3 in different bone-related diseases in combination with in vitro experiments and animal models. Then, we summarize and categorize the drugs that target Stat3, providing potential therapeutic strategies for their use in bone-related diseases. In conclusion, Stat3 could be a future target for bone-related diseases.